Propostas pedagógicas para o ensino de Botânica em uma escola de tempo integral - Peixoto, Erica de Souza (2023)
The present work deals with a research that aimed to reflect on the use of ecological trails and workshops for the production of herbarium specimens as teaching activities in the botanical theme. The main objective was to investigate whether the use of these pedagogical approaches contributes to stimulating students' curiosity and interest in Botany content, even within the curriculum of the New High School system. The research was conducted in a qualitative-quantitative manner with students from the 2nd year of high school at a Full-Time School in the city of Miranda-MS. Four stages were carried out: a pre-test for preliminary analysis of students' knowledge, two trails (one around the school and another in a biological reserve), a workshop for the production of herbarium specimens and for the identification of collected species using digital applications, and a post-test questionnaire to analyze the impact of these proposals on student learning. After completing all stages, it was observed that the didactic proposals, taught in a meaningful, contextualized, and active manner, using diversified strategies, as well as the direct contact with plants from the Pantanal and Cerrado biomes, were able to stimulate interest in this approach among the students and provide teachers with means that can facilitate and encourage the teaching-learning process of botany, whether in regular classes or in formative routes. Learning about Botany in a practical and dynamic way is fundamental to disseminate this important area of Biology. Keywords: Teaching of Botany; Interpretive trails; Plants; Miranda-MS.